Sintok (Entada spiralis ridl.): natural sources of antioxidant compounds - Syed Mohamed, Sharifah Nurul Akilah; Mat So'ad, Siti Zaiton (IIUM Press, International Islamic University Malaysia, 2017)
Sintok or Beluru, scientifically known as Entada spiralis Rid!. is belongs to Leguminoceae. This plant is a huge liana with woody climber that grows wildly in Malaysia. Sintok is found natively to Peninsular Malaysia, Indonesia, Singapore and Thailand. This species have been characterized by its bipinnate leaves with small flowers. As recognized being as one of Mimosoideae sub-family, stamens of flower is the main parts of attraction. The pods of seed are curled with 5-1 l very large seeds to each pod. In Malay aromatheraphy, Sintok plant is an important element that used during post-natal bath and body cleansing shampoo (FRIM Flora Database). This plant also acknowledged by Universaiti Utara Malaysia (UUM Sintok) as their icon as UUM located in Sintok, name that derived from this plant.